Exploration of β-Ga2O3 Ceramics Synthesized via Solid-State Method - A. Bakytkyzy; Z.T. Karipbayev; Y. Suchikova; A.B. Usseinov; T.A. Koketai; N.K. Mussabek; A.I. Popov (Қарағанды университетінің хабаршысы. Физика сериясы)
β-Ga2O3 ceramic was synthesized using the solid-state method, a well-established technique for creating ceramic materials with controlled composition and structure. The process began by pressing gallium oxide (Ga2O3) powder into a unified form, ensuring even distribution and compactness of the material. This pressed form was then subjected to annealing at 1400 °C for 10 hours, a critical step facilitating the formation of a stable and crystalline β-Ga